High-temperature-resistant aerogel felt and preparation method thereof

By using a combination of agar powder of specific particle size and sunscreen in aerogel felt, converting it into carbon material through heat treatment, and combining it with silica sol-gel reaction, aerogel felt with excellent high-temperature resistance was prepared, which solved the problem of insufficient performance of aerogel materials at high temperatures and expanded its application range.

CN120590142APending Publication Date: 2025-09-05IBIH ADVANCED MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510598252.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing aerogel materials have poor heat resistance and mechanical properties at high temperatures, and the sunscreen dispersion effect is not significant, which limits their application range.

Method used

Agar powder with a specific particle size is used as a carrier, the sunscreen is evenly dispersed into the substrate, and heat-treated under an inert atmosphere to convert the agar into carbon material. Combined with the silica sol-gel reaction, a high-temperature resistant aerogel felt is prepared in one step.

Benefits of technology

The excellent high temperature resistance and mechanical properties of aerogel felt are achieved, and its application range is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005395207180000081
    Figure BDA0005395207180000081
  • Figure BDA0005395207180000091
    Figure BDA0005395207180000091
Patent Text Reader

Abstract

The invention relates to the field of aerogel composite materials, and discloses a high-temperature-resistant aerogel felt and a preparation method thereof. The method comprises the following steps: (1) in the presence of water, performing first mixing on agar powder and an opacifying agent to obtain a mixture I; (2) filling the mixture I into a base material I to obtain a base material II; carrying out heat treatment on the base material II to obtain a base material III; (3) carrying out gel reaction on the base material III and silica sol to obtain a wet gel composite material; and (4) sequentially aging and drying the wet gel composite material. The method provided by the invention can be used for preparing the aerogel felt with excellent high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aerogel composite materials, in particular to high-temperature resistant aerogel felt and a preparation method thereof. Background Art

[0002] Aerogel materials have attracted widespread attention due to their ultra-low density and high specific surface area. Although aerogels with high porosity exhibit low solid-phase and gas-phase heat transfer, they experience high radiative heat transfer at high temperatures. Furthermore, aerogels can sinter and undergo structural changes under these conditions, resulting in relatively poor high-temperature resistance. Furthermore, aerogels also have relatively poor mechanical properties, further limiting their application.

[0003] With the rising price of raw materials, loading aerogel on substrates such as glass fiber felt, ceramic fiber felt, and melamine sponge can not only increase the mechanical strength of aerogel materials, but also reduce costs, thereby expanding the application range of aerogel materials.

[0004] As for the problem of high temperature resistance of aerogel materials, generally speaking, the introduction of sunscreens in the process of preparing aerogel materials can play a role of reflection, absorption and re-scattering, which can effectively reduce the radiation conduction of aerogels at high temperatures, thereby improving the high temperature resistance of aerogel materials.

[0005] However, although the introduction of sunscreens can solve the problem of high temperature resistance of aerogels, the dispersion of sunscreens is still a problem during the addition process.

[0006] Currently, methods for dispersing sunscreen agents include: (1) dispersing sunscreen agents such as iron oxide by adding sodium tripolyphosphate or sodium hexametaphosphate; (2) applying negative pressure during the addition of the sunscreen agent to the substrate; and (3) homogenizing the sunscreen solution before adding it to the substrate. However, the aforementioned methods do not significantly disperse the sunscreen agent.

[0007] CN104291773A discloses a method for preparing a low-density, ultra-high-temperature stable, strong radiation-resistant bulk material, which is characterized by the following specific steps: (1) placing agar powder in a ratio of 2.5-3.5wt% into 70-80°C hot water and mixing and stirring until uniform; (2) placing hydrophilically treated titanium dioxide and potassium titanate whisker powder materials into the solution prepared in step (1), stirring for 40 minutes until the mixture is uniform; (3) adjusting the pH value of silicon oxide hydrosol to neutral, adding it to the mixed solution prepared in step (2), and stirring for 20 minutes until the mixture is uniform; (4) pouring the mixed solution obtained in step (3) into a pre-prepared mold, and after cooling, the agar solidifies and is cast into shape; (5) placing the cooled colloidal material into a refrigerator and freezing it for 10 hours, and then placing it into a freeze-drying equipment, and vacuum drying it at about -40°C for 30 hours to obtain a strong radiation-resistant bulk material. Although this prior art can solve the problem of poor dispersion of powder materials in matrix materials, the mechanical properties of the aerogels prepared by this prior art are poor, which further limits the scope of use of the aerogel materials. Summary of the Invention

[0008] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a method for preparing an aerogel felt with excellent high-temperature resistance.

[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a high temperature resistant aerogel felt, the method comprising:

[0010] (1) In the presence of water, agar powder and a sunscreen are first mixed to obtain a mixture I; the agar powder has an average particle size of 45-160 μm, a loss on drying of ≤10 wt%, and a residue on ignition (ash) of 2.8-4 wt%; and the weight ratio of the agar powder to the sunscreen is 1:1-30;

[0011] (2) filling the mixture I into a substrate I to obtain a substrate II; and heat-treating the substrate II to obtain a substrate III; the filling position of the mixture I is 3 / 8-5 / 8h from the surface of the substrate I in the thickness direction h;

[0012] The heat treatment conditions include: in an inert atmosphere, a temperature of 250-450° C., and a time of 1-5 hours;

[0013] (3) subjecting the substrate III to a gel reaction with the silica sol to obtain a wet gel composite material;

[0014] (4) The wet gel composite material is aged and dried in sequence.

[0015] The second aspect of the present invention provides a high-temperature resistant aerogel felt prepared by the method described in the first aspect.

[0016] The present application uses agar powder of a specific particle size as a carrier to evenly disperse the sunscreen into a substrate, and heat-treats the substrate filled with the sunscreen at a certain temperature to remove the agar, while converting the agar into a carbon material as a sunscreen; an aerogel felt with excellent high-temperature resistance can be prepared in one step without changing the subsequent preparation process. DETAILED DESCRIPTION

[0017] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0018] As mentioned above, the first aspect of the present invention provides a method for preparing a high temperature resistant aerogel felt, the method comprising:

[0019] (1) In the presence of water, agar powder and a sunscreen are first mixed to obtain a mixture I; the agar powder has an average particle size of 45-160 μm, a loss on drying of ≤10 wt%, and a residue on ignition (ash) of 2.8-4 wt%; and the weight ratio of the agar powder to the sunscreen is 1:1-30;

[0020] (2) filling the mixture I into a substrate I to obtain a substrate II; and heat-treating the substrate II to obtain a substrate III; the filling position of the mixture I is 3 / 8-5 / 8h from the surface of the substrate I in the thickness direction h;

[0021] The heat treatment conditions include: in an inert atmosphere, a temperature of 250-450° C., and a time of 1-5 hours;

[0022] (3) subjecting the substrate III to a gel reaction with the silica sol to obtain a wet gel composite material;

[0023] (4) The wet gel composite material is aged and dried in sequence.

[0024] It should be noted that the water in step (1) is used as a solvent. The present invention has no particular limitation on its amount. Those skilled in the art can select it according to the technical means known in the art. The following text of the present invention exemplifies a preferred specific embodiment, which should not be understood by those skilled in the art as limiting the present invention.

[0025] Preferably, the average particle size of the sunscreen is 2-8 μm.

[0026] More preferably, the average particle size of the sunscreen is 2-4 μm. The inventors of the present invention have found that under this preferred condition, the product obtained by the method of the present invention has better high temperature resistance.

[0027] Preferably, the sunscreen is selected from at least one of aluminum oxide, titanium oxide, and magnesium oxide.

[0028] Preferably, the substrate I is selected from one of needle-punched felt and wet-laid felt.

[0029] Preferably, the first mixing conditions include: stirring at a speed of 1000-10000 rpm, a temperature of 60-90° C., and a time of 10-120 min.

[0030] Further preferably, the first mixing is carried out under stirring conditions at a speed of 3000-7000 rpm, a temperature of 60-90° C., and a time of 10-60 min. The inventors of the present invention have found that under this preferred condition, the product obtained by the method of the present invention has better high temperature resistance.

[0031] Preferably, the gel reaction conditions include: temperature of 15-45° C. and time of 0.1-2 h.

[0032] According to a preferred embodiment, the silica sol is prepared by a method comprising the following steps:

[0033] (i) hydrolyzing a silicon source with water in the presence of a solvent and a catalyst A to obtain a mixture A;

[0034] (ii) In the presence of catalyst B, the mixture A is subjected to a sol reaction.

[0035] It should be noted that the present invention has no particular limitation on the amount of the solvent used in step (i), and those skilled in the art can select it according to technical means known in the art. A preferred specific embodiment is exemplified below in the present invention, which should not be understood by those skilled in the art as limiting the present invention.

[0036] Preferably, the weight ratio of the silicon source, the water, the catalyst A, and the catalyst B is 100:1-100:0.01-1:0.5-30. Preferably, the weight ratio of the silicon source, the water, the catalyst A, and the catalyst B is 100:20-80:0.01-0.5:0.5-30.

[0037] Preferably, the hydrolysis reaction is carried out under stirring at a speed of 100-2000 rpm, a temperature of 30-60° C., and a time of 10-100 min.

[0038] Preferably, the sol reaction conditions include: being carried out under vacuum conditions, a pressure of 0.01-0.1 MPa, and a time of 1-30 min.

[0039] Preferably, the solvent is selected from at least one of C1-C6 linear monohydric alcohols, more preferably, the solvent is selected from at least one of methanol, ethanol, and propanol.

[0040] Preferably, the silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, and dimethyldiethoxysilane.

[0041] Preferably, the catalyst A and the catalyst B are each independently selected from at least one of oxalic acid, hydrochloric acid, hydrofluoric acid, sodium bicarbonate, sodium hydroxide, ammonia water, ammonium fluoride, and sodium fluoride.

[0042] According to a particularly preferred embodiment, the catalyst A is selected from at least one of oxalic acid, hydrochloric acid, and hydrofluoric acid; and the catalyst B is selected from at least one of sodium bicarbonate, sodium hydroxide, ammonia water, ammonium fluoride, and sodium fluoride.

[0043] It should be noted that the present invention has no particular limitation on the usage ratio of the substrate III to the silica sol, as long as the substrate III can be immersed in the silica sol.

[0044] Preferably, the aging conditions include: temperature of 45-65° C. and time of 10-30 h.

[0045] Preferably, the drying conditions include: supercritical drying, a pressure of 4-15 MPa, a temperature of 30-300° C., and a time of 1-9 h.

[0046] As mentioned above, the second aspect of the present invention provides a high temperature resistant aerogel felt prepared by the method described in the first aspect.

[0047] The present invention will be described in detail below through examples.

[0048] In the following examples, unless otherwise specified, all raw materials used were commercially available.

[0049] raw material:

[0050] Agar powder:

[0051] Agar powder I: average particle size 90 μm, loss on drying 8 wt %, residue on ignition (ash) 3.7 wt %, purity 99%, food grade, purchased from Suzhou Xuanqinrun Trading Co., Ltd.

[0052] Agar powder II: average particle size 90 μm, loss on drying 13 wt %, residue on ignition (ash) 3.3 wt %, purity 100%, food grade, purchased from Shandong Haoshuo Biotechnology Co., Ltd.

[0053] Agar powder III: average particle size 90 μm, loss on drying 10 wt %, residue on ignition (ash) 2.6 wt %, purity 99.5%, food grade, purchased from Henan Letai Food Co., Ltd.

[0054] Sunscreen:

[0055] Sunscreen I: aluminum oxide, average particle size 2 μm, purchased from Guangxi Kelifang New Materials Co., Ltd.

[0056] Sunscreen II: aluminum oxide, average particle size 4 μm, purchased from Guangzhou Suifeng Chemical Co., Ltd.

[0057] Substrate I:

[0058] The needle-punched felt, with a thickness of 10 cm, was purchased from Nanjing Yuanzheng Fiberglass Co., Ltd.

[0059] Preparation of silica sol I

[0060] (i) hydrolyzing 222 g of ethyl orthosilicate (silicon source) with 111 g of deionized water in the presence of 1000 g of ethanol (solvent) and 0.1 g of 37 wt % hydrochloric acid (catalyst A) to obtain a mixture A;

[0061] The hydrolysis reaction conditions are as follows: under stirring conditions, the stirring speed is 2000 rpm, the temperature is 30°C, and the time is 60 min;

[0062] (ii) subjecting the mixture A to a sol reaction in the presence of 10 g of 2 wt % sodium hydroxide (catalyst B) to obtain silica sol I;

[0063] The weight ratio of silicon source, water, catalyst A and catalyst B is 100:50:0.017:0.9;

[0064] The conditions of the sol reaction are: carried out under vacuum conditions, a pressure of 0.01 MPa, and a time of 15 minutes.

[0065] Example 1

[0066] (1) In the presence of 100 g of deionized water, 0.3 g of agar powder 1 and 3 g of sunscreen 1 were first mixed to obtain a mixture 1;

[0067] The weight ratio of agar powder to sunscreen is 1:10;

[0068] The first mixing conditions are: stirring at a speed of 5000 rpm, a temperature of 90° C., and a time of 10 min;

[0069] (2) filling the mixture I into the needle-punched felt (substrate I) to obtain substrate II; and heat-treating substrate II to obtain substrate III; the filling position of the mixture I is 3 / 8-5 / 8h from the surface of the substrate I in the thickness direction h;

[0070] The heat treatment conditions were as follows: inert atmosphere (N2), temperature 300 °C, time 2 h;

[0071] (3) subjecting the substrate III to a gel reaction with the silica sol I to obtain a wet gel composite material;

[0072] The conditions for the gelation reaction were: temperature 30°C, time 1 h;

[0073] (4) aging and drying the wet gel composite material in sequence to prepare an aerogel felt Z1;

[0074] The aging conditions are: temperature 60°C, time 10h;

[0075] The drying conditions are: supercritical drying, pressure of 15 MPa, temperature of 280°C, and time of 1 h.

[0076] Example 2

[0077] This example is carried out in a similar manner to Example 1, except that:

[0078] In step (1), the sunscreen I is replaced by the sunscreen II, and the other conditions are the same as those in Example 1, to prepare the aerogel felt Z2.

[0079] Comparative Example 1

[0080] This example is carried out in a similar manner to Example 1, except that:

[0081] In step (1), agar powder I was replaced by agar powder II by weight, and the other conditions were the same as those in Example 1 to prepare aerogel felt DZ1.

[0082] Comparative Example 2

[0083] This example is carried out in a similar manner to Example 1, except that:

[0084] In step (1), agar powder I was replaced by agar powder III by weight, and the other conditions were the same as those in Example 1 to prepare aerogel felt DZ2.

[0085] Comparative Example 3

[0086] This example is carried out in a similar manner to Example 1, except that:

[0087] In step (1), the amount of agar powder I is adjusted so that the weight ratio of agar powder to sunscreen is 1:50, and the other conditions are the same as those in Example 1 to prepare aerogel felt DZ3.

[0088] Comparative Example 4

[0089] This example is carried out in a similar manner to Example 1, except that:

[0090] In step (2), the temperature in the heat treatment conditions was adjusted to 500° C., and the other conditions were the same as those in Example 1, to prepare aerogel felt DZ4.

[0091] Test Case

[0092] The aerogel felts prepared in the examples and comparative examples were tested for high temperature resistance according to the following method. The results are shown in Table 1.

[0093] (1) Thermal conductivity at 300°C: Tested according to the method in GB / T 10294-2008.

[0094] (2) Thermal conductivity at 500°C: Tested according to the method in GB / T 10294-2008.

[0095] Table 1

[0096]

[0097]

[0098] It can be seen from the results in Table 1 that the aerogel felt prepared by the method provided by the present invention can obtain excellent high temperature resistance.

[0099] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A method for preparing high temperature resistant aerogel felt, characterized in that: The method includes: (1) In the presence of water, agar powder and a sunscreen are first mixed to obtain a mixture I; the agar powder has an average particle size of 45-160 μm, a loss on drying of ≤10 wt%, and a residue on ignition of 2.8-4 wt%; and the weight ratio of the agar powder to the sunscreen is 1:1-30; (2) filling the mixture I into a substrate I to obtain a substrate II; and heat-treating the substrate II to obtain a substrate III; the filling position of the mixture I is 3 / 8-5 / 8h from the surface of the substrate I in the thickness direction h; The heat treatment conditions include: in an inert atmosphere, a temperature of 250-450° C., and a time of 1-5 hours; (3) subjecting the substrate III to a gel reaction with the silica sol to obtain a wet gel composite material; (4) The wet gel composite material is aged and dried in sequence.

2. The method according to claim 1, wherein The average particle size of the sunscreen is 2-8 μm; and / or, The sunscreen is selected from at least one of aluminum oxide, titanium oxide and magnesium oxide.

3. The method according to claim 1 or 2, wherein: The first mixing conditions include: stirring at a speed of 1000-10000 rpm, a temperature of 60-90° C., and a time of 10-120 min.

4. The method according to any one of claims 1 to 3, wherein: The silica sol is prepared by a method comprising the following steps: (i) hydrolyzing a silicon source with water in the presence of a solvent and a catalyst A to obtain a mixture A; (ii) In the presence of catalyst B, the mixture A is subjected to a sol reaction.

5. The method according to claim 4, wherein The weight ratio of the silicon source, the water, the catalyst A and the catalyst B is 100:1-100:0.01-1:0.5-30.

6. The method according to claim 4 or 5, wherein: The hydrolysis reaction conditions include: carrying out the reaction under stirring conditions at a stirring speed of 100-2000 rpm, a temperature of 30-60° C., and a time of 10-100 min; and / or, The conditions of the sol reaction include: being carried out under vacuum conditions, a pressure of 0.01-0.1 MPa, and a time of 1-30 minutes.

7. The method according to any one of claims 4 to 6, wherein: The solvent is selected from at least one of C1-C6 linear monohydric alcohols; and / or, The silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, and dimethyldiethoxysilane.

8. The method according to any one of claims 4 to 7, wherein: The catalyst A and the catalyst B are each independently selected from at least one of oxalic acid, hydrochloric acid, hydrofluoric acid, sodium bicarbonate, sodium hydroxide, ammonia water, ammonium fluoride, and sodium fluoride.

9. The method according to any one of claims 1 to 8, wherein: The aging conditions include: temperature of 45-65° C. and time of 10-30 h; and / or, The drying conditions include: supercritical drying, a pressure of 4-15 MPa, a temperature of 30-300° C., and a time of 1-9 hours.

10. High temperature resistant aerogel felt prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of intense-radiation-resistant block material stable having low density and stability at superhigh temperature

    CN104291773A